The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1093/intqhc/mzr083
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events in Spanish intensive care units: the SYREC study

Abstract: The individual risk for incidents in critical patients is high. Many incidents did not harm patients, some caused damage and a few were related to the patient's death. Most incidents were considered avoidable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
3
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 27 publications
1
25
3
8
Order By: Relevance
“…In this study notifi ed incidents predominated in the age group from 13 to 59 years 377 (51.8 %), while patients over 60 years old were 303 (41.6%) of the notifi ed incidents. These statistics don't match with the data found in other research where incidents predominated in patients of more than 62 years old (16) .…”
Section: Departmentscontrasting
confidence: 95%
See 2 more Smart Citations
“…In this study notifi ed incidents predominated in the age group from 13 to 59 years 377 (51.8 %), while patients over 60 years old were 303 (41.6%) of the notifi ed incidents. These statistics don't match with the data found in other research where incidents predominated in patients of more than 62 years old (16) .…”
Section: Departmentscontrasting
confidence: 95%
“…When analysing the incidents notifi ed in relation to gender, we observed that there was no signifi cant diff erence between men 377 (50.4%) and women 372 (49.6%), confi rming the Spanish study that didn't fi nd any significant diff erence between the genders (16) . In this study notifi ed incidents predominated in the age group from 13 to 59 years 377 (51.8 %), while patients over 60 years old were 303 (41.6%) of the notifi ed incidents.…”
Section: Departmentsmentioning
confidence: 57%
See 1 more Smart Citation
“…The complexity of care for critical patients requires advanced technology and specialized professionals able to immediately intervene in any change in their clinical condition 1,2,3,4 . Intensive care units (ICU) concentrate patients with this profile, however, there is a high frequency of adverse events in hospital wards 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…James claimed that the Institute of Medicine's report in 2000 severely underestimated the prevalence of medical errors and their effects on morbidity and mortality [5]. Medical errors affected from 26.8 [1] to 58 % [6] of the patients, including one-third from medication errors alone [4], and may contribute to mortality [1]. Understanding medical errors is complex and involves country (or health care system), hospital, group (ICU culture and other ICU factors) and individual levels [7].…”
Section: How Important Is the Problem?mentioning
confidence: 99%